Impact assessment of Chinese mitten crab polyculture on saline-alkali rice fields based on food web models - Liang Yue; Shipeng Dong; Feng Liu; Dapeng Liu; Hongwei Shan; Fang Wang (Aquaculture Reports)
In China, the introduction of Chinese mitten crabs Eriocheir sinensis into saline-alkali rice fields has improved both soil utilization and quality. To promote the development and adoption of this novel rice-cropping mode, this study developed Ecopath models for two contrasting systems, rice-crab integrated farming (RC) and rice monoculture (R). Each system’s trophic structure, energy flow, and carrying capacity were analyzed and evaluated. The results showed that introducing Chinese mitten crabs increased both the biomass and utilization of rice, with its biomass 4.81 % higher in the RC than R system, with an ecological efficiency value that was 0.15 higher. Both systems exhibited similar trophic structures with three integer trophic levels. Total system throughput in the RC system was 21 368 g m−2 130 days−1, exceeding the 13 730 g m−2 130 days−1 in the R system. The ratio of total net primary production to the sum of all respiratory flows in the RC system was 2.390, this lower than the 4.006 in the R system, indicating that the former’s scale and development degree surpass the latter’s. In the RC system, Chinese mitten crabs primarily utilized detrital energy, with the energy flowing from detritus to trophic level II accounting for 41.84 % of the total energy input into the detritus group; that value is much higher than the 27.15 % in the R system. The carrying capacity of crabs was 33.66 g m−2. Overall, after polyculture with Chinese mitten crabs and the addition of feed, the rice farming system’s trophic structure did not change significantly, yet more energy was directed towards production, and the current polyculture ratio is reasonable. This study not only provides scientific evidence for the development of the rice-crab integrated farming model in saline-alkali soils, but also enriches the application potential of food web modeling in integrated rice-fish farming systems.